Volume 3: Nonlinear Estimation and Control; Optimization and Optimal Control; Piezoelectric Actuation and Nanoscale Control; Ro 2013
DOI: 10.1115/dscc2013-3950
|View full text |Cite
|
Sign up to set email alerts
|

A Random Matrix Approach to Manipulator Jacobian

Abstract: Traditional kinematic analysis of manipulators, built upon a deterministic articulated kinematic modeling often proves inadequate to capture uncertainties affecting the performance of the real robotic systems. While a probabilistic framework is necessary to characterize the system response variability, the random variable/vector based approaches are unable to effectively and efficiently characterize the system response uncertainties. Hence in this paper, we propose a random matrix formulation for the Jacobian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The reduced Jacobian matrix has right and left Eigen-vectors as (4) which is resulting in participation factors that can be defined as [21], [22].…”
Section: Modes and Voltage Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced Jacobian matrix has right and left Eigen-vectors as (4) which is resulting in participation factors that can be defined as [21], [22].…”
Section: Modes and Voltage Stabilitymentioning
confidence: 99%
“…Generally, the modal analysis relies on the matrix of diagonal eigen-values of matrix J R (). Thus, the reduced Jacobian matrix determines the condition of the given electrical system with respect to voltage stability [22].…”
Section: = ɳmentioning
confidence: 99%
“…In this section, our random matrix formulation of the manipulator Jacobian matrix developed in [4], [5] is generalized to dynamic EOM of the robotic systems. The EOM of the deterministic mean dynamic system can be expressed as:…”
Section: Random Matrix Formulationmentioning
confidence: 99%
“…• Computational efficiency. In this paper, we generalize our RM-based uncertainty model for manipulator Jacobian matrix, developed in [4], [5], that is based on the non-parametric probabilistic model proposed by Soize [6], [7], to dynamic equations of motion (EOM) of the robotic systems. This provides a systematic approach that adequately satisfies the requirements noted above and can be beneficial in the design procedure of the complex dynamic systems (from the uncertainty perspective).…”
Section: Introductionmentioning
confidence: 99%
“…The robustness of the second-order approximation as well as its superiority compared to the first-order method was verified in different numerical examples. Sovizi et al [14][15][16][17][18] proposed an uncertainty characterization method in complex robotic manipulators based on the random matrix theory (RMT). It was shown that RMT-based models can appropriately capture the uncertainty only using limited information about the system variation.…”
Section: Introductionmentioning
confidence: 99%